2010
DOI: 10.2139/ssrn.2001402
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing and Cross-Border Entry in European Banking

Abstract: Standard-Nutzungsbedingungen: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…In addition, though the United States represents an overwhelmingly popular target market for cross‐border deals, our findings on flows in the direction of regulatory arbitrage remain when we exclude U.S. banks as targets or acquirers. Finally, we test the robustness of our results to the inclusion of controls for the quality of information sharing in the target country, which has been shown to affect cross‐border bank entry (Bouckaert and Degryse (), Giannetti, Jentzsch, and Spagnolo ()). Our results continue to go through.…”
Section: Additional Robustness Testsmentioning
confidence: 97%
“…In addition, though the United States represents an overwhelmingly popular target market for cross‐border deals, our findings on flows in the direction of regulatory arbitrage remain when we exclude U.S. banks as targets or acquirers. Finally, we test the robustness of our results to the inclusion of controls for the quality of information sharing in the target country, which has been shown to affect cross‐border bank entry (Bouckaert and Degryse (), Giannetti, Jentzsch, and Spagnolo ()). Our results continue to go through.…”
Section: Additional Robustness Testsmentioning
confidence: 97%
“…In addition to competitive disadvantages in relation to incurring greater risks of incorrectly estimating a borrower's credit risk, without relevant information on borrowers new market entrants would be likely to attract precisely those who were rejected by existing lenders in the market. 21 This circumstance has induced recent literature to conclude that information sharing, market structure, and competitive conduct are intrinsically intertwined in the financial services market and, from the standpoint of industrial organisation, the availability of information shared by the sector can affect foreign lenders' choice not only of whether to entry another jurisdiction but also the mode of doing it, i. e. whether through the cross-border provision of services, the setting-up of branches or subsidiaries, or through mergers and acquisitions. 22 Therefore, on the one hand such strategies may well have the potential to influence the intensity of competition in national markets and among national providers.…”
Section: Competitionmentioning
confidence: 99%
“…5 1 For example, in a recent paper about the banking industry, Giannetti et al (2010) found that the green…eld/merger entry decision by banks in European countries is a¤ected by the type of credit register (private or public) in every country. This di¤erence a¤ects essentially the entry barriers to green…eld entry (or creates a di¤erent "demand de…cit" as found by Foster et al (2010)) that my model is taking into account.…”
Section: Counterfactual Policy Experimentsmentioning
confidence: 99%